A Genetic Toolkit for Simultaneous Generation of - and -Expressing Clones in Selected Cell Types in - Kota Banzai; Ping Shen; Daichi Kamiyama (Neuroscience Insights, 2022)
Visualization and manipulation of defined motoneurons have provided significant insights into how motor circuits are assembled in Drosophila . A conventional approach for molecular and cellular analyses of subsets of motoneurons involves the expression of a wide range of UAS transgenes using available GAL4 drivers (eg, eve promoter-fused GAL4 ). However, a more powerful toolkit could be one that enables a single-cell characterization of interactions between neurites from neurons of interest. Here we show the development of a UAS > LexA > QF expression system to generate randomly selected neurons expressing one of the 2 binary expression systems. As a demonstration, we apply it to visualize dendrite-dendrite interactions by genetically labeling eve + neurons with distinct fluorescent reporters.